Water for the thousand millions - Pacey, Arnold (Pergamon Press, 1977)
"Millions of Americans take personality tests each year: to get a job, to pursue an education, to settle a legal dispute, to better understand themselves and others." "Combining cutting-edge research, engaging reporting, and absorbing history, Paul uncovers the way these allegedly neutral instruments are in fact shaped by the agendas of industry and government. She documents the dangers of their intrusive questions, biased assumptions, and limiting labels. And she exposes the flawed theories and faulty methods that render their results unreliable and invalid. Personality tests, she contends, produce descriptions of people that are nothing like human beings as they actually are: complicated, contradictory, changeable across time and place."--BOOK JACKET.